Penerapan Strategi Pembelajaran Kooperatif Tipe Think Pair And Share (Tps) Mata Pelajaran IPS Dengan Materi Bentuk Muka Bumi Dan Aktifitas Penduduk Di Indonesia Siswa Kelas VII Di SMP Muhammadiyah 8 Surakarta - WIDI HAPSARI, NUR MALITA, Drs. Suharjo, M.S (2015)
This study aims to determine the level of understanding of students in social studies with the material shape of the earth and the activities of the population in Indonesia class VII in SMP Muhammadiyah Surakarta 8 before and after the application of Learning Strategy and Think Pair Share (TPS). This research subject is class VII VII namely class A, class B and class VII VII C totaling 69 students. A Class VII as the seventh grade while the control class A and class C as the experimental class VII. Experimental class learning is done by applying the TPS strategy. While classroom learning control is done using conventional methods or lectures. Results of hypothesis testing data using Test Independent Sample T-Test, and Mann-Whitney test. The research data showed the students' understanding before the application of learning strategies and Think Pair Share (TPS) seen on learning outcomes, the experimental class to obtain an average value Pre Test 65 with the lowest score of 44 and the control class received grades Pre Test average of 66.52 with a value 44. Judging the results of the lowest average class pretest experimental and control classes can be concluded that the level of understanding of students on the material shape of the earth and the activities of the population in Indonesia is still low. And the level of understanding students' learning strategy after the implementation of TPS seen from the experimental class learning obtain an average value of 71.77 Post Test with the highest grade 93 and grade control to obtain an average value of 68.14 Post Test with the highest score of 83. Class experiments using TPS strategy gained as much as 6.77% increase while the control group increased as much as 3.62%.